Rancang Bangun Aplikasi Registrasi dan Inventarisasi Koleksi Museum Teknoform pada Universitas Dinamika - Nugraha, Ade Prisma; Tjandrarini, A. B.; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
Museum Teknoform is one of the many technology-themed museums owned by Dinamika University. There have some problem at the Museum Teknoform that have been described. First, collection registration using manual method with Microsoft Excel, so the data cannot be accessed simultaneously because there is no centralized database and it cause storage errors when access the data. Second, the inventory of collections by the Museum Teknoform has not yet been carried out, as a result of incomplete information, such as no numbering or coding of item and no information describing the items, officers do not know for sure about the quantity and condition of the item. This is very influential in making collentions reports. Where complete information is needed to make it easier to compile reports on the development of collection owned by the Museum Teknoform. Third, there are many collections in the Museum Teknoform that do not have a catalog, which prevents the Museum Teknoform from accessing information about the collection quickly and precisely. Based on the explanation abov, Museum Teknoform needs a system that can help Museum Teknoform be able to solve the problems found in the company by designing and building a registration and inventory application of Museum Teknoform collection.